Brand Interactivity and Involvement on Consumer Brand Engagement and Brand Loyalty: Mediated by Brand Trust Study on Skintific - Alfira Auliyaa Assyari; Wibisono Soediono (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aimed to determine the effect of brand interactivity and involvement in driving social media customer brand engagement and brand loyalty with the mediating effect of brand trust on the beauty brand Skintific. primary data was gathered using questionnaires with 7 Likert scales online. The sampling method uses the Non-probability Sampling purposive sampling technique. The data processing results were obtained from 226 respondents who are users of Skintific and followers of Skintific on TikTok and Instagram. Using the Second Order Construct Analysis method with the WARP-PLS 8.0 program, which is part of the Structural Equation Model (SEM), The results of this study indicate that brand interactivity and brand involvement have a positive and significant effect on customer brand engagement. Furthermore brand trust partially mediates the influence of customer brand engagement through brand loyalty for Skintific brand.